2011
DOI: 10.1128/aac.00045-11
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Inhibitors Increase the Susceptibility of Bacterial Biofilms to Antibiotics In Vitro and In Vivo

Abstract: Although the exact role of quorum sensing (QS) in various stages of biofilm formation, maturation, and dispersal and in biofilm resistance is not entirely clear, the use of QS inhibitors (QSI) has been proposed as a potential antibiofilm strategy. We have investigated whether QSI enhance the susceptibility of bacterial biofilms to treatment with conventional antimicrobial agents. The QSI used in our study target the acylhomoserine lactone-based QS system present in Pseudomonas aeruginosa and Burkholderia cepac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
394
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(412 citation statements)
references
References 46 publications
14
394
1
3
Order By: Relevance
“…In tests where treatments were initiated 11 days postimplant, they were not beneficial, indicating the need to intervene before bacteria enter a chronic infection state and/or before the host immune system walls off the infection. In separate studies, combinatorial application of the previously identified QSI compounds baicalin hydrate, hamamelitannin, and cinnamaldehyde with antibiotics was tested on Burkholderia spp., S. aureus, and P. aeruginosa to measure viable counts of bacteria in biofilms and in animal models of infection (283,284). Synergistic effects were most pronounced in Burkholderia cepacia biofilms treated with baicalin hydrate combined with tobramycin, which resulted in an additional 2-log decrease in viable cell counts compared to tobramycin treatment alone.…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 99%
“…In tests where treatments were initiated 11 days postimplant, they were not beneficial, indicating the need to intervene before bacteria enter a chronic infection state and/or before the host immune system walls off the infection. In separate studies, combinatorial application of the previously identified QSI compounds baicalin hydrate, hamamelitannin, and cinnamaldehyde with antibiotics was tested on Burkholderia spp., S. aureus, and P. aeruginosa to measure viable counts of bacteria in biofilms and in animal models of infection (283,284). Synergistic effects were most pronounced in Burkholderia cepacia biofilms treated with baicalin hydrate combined with tobramycin, which resulted in an additional 2-log decrease in viable cell counts compared to tobramycin treatment alone.…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 99%
“…One of the major reasons for the increase in resistance to antibiotics is the expression of different genes that encodes a set of protein that confers the microbial community with this character. In addition to genetic factors which involve the expression of vital genes in favor of the microorganisms, the extra polymeric matrix prevents the penetration of the antimicrobial agents in to biofilms and quorum sensing is another vital factor that favors the microbial communities within biofilms [92]. The biofilm structure enables the pathogens to tolerate the antimicrobial agent which is an in built character of the bacterial biofilms [93].…”
Section: Biofilms and Antimicrobial Resistancementioning
confidence: 99%
“…Garlic extract has also been shown to increase the susceptibility of P. aeruginosa to tobramycin and to phagocytosis Rasmussen et al, 2005), and, in the murine model of lung infection, it has been shown to significantly reduce mortality rate and promote rapid clearing of P. aeruginosa from the lung . Furthermore, garlic extract blocks P. aeruginosa and Acinetobacter baumannii quorum sensing systems Harjai et al, 2010;Rasmussen et al, 2005;Sarkar & Chakraborty, 2008), which have been shown to control biofilm development (Brackman et al, 2011;Davies et al, 1998).…”
Section: Introductionmentioning
confidence: 99%